Tourism Development Strategy as a Lever of Local Original Income - Abdul Hafiz; Abdelsalam Alnaddaf; Shaimaa Adel Yaseen Saleh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze tourism development strategies in increasing Local Own-Source Revenue in Bandar Lampung City through tourism promotion, infrastructure development, stakeholder collaboration, and community-based tourism approaches to support sustainable regional economic growth and regional fiscal independence. Methodology: This study employed a descriptive qualitative approach using a case study method. Data were collected through semi-structured interviews, observations, and documentation involving Tourism Office officials, tourism destination managers, tourism business actors, and community representatives. The study used interview guidelines, observation sheets, and documentation checklists. Data were analyzed using the Miles and Huberman interactive analysis model through data reduction, data display, and conclusion drawing techniques. Main Findings: The findings revealed that tourism development strategies contributed significantly to increasing Own-Source Revenue through tourism promotion, infrastructure improvement, stakeholder collaboration, and community-based tourism development. Digital promotion increased tourist visits, while infrastructure enhancement improved tourist satisfaction and accessibility. However, several obstacles remained, including limited budgets, weak stakeholder coordination, low human resource quality, and environmental management issues affecting tourism competitiveness and sustainable tourism development. Novelty/Originality of this study: The novelty of this study lies in its comprehensive analysis integrating institutional roles, stakeholder collaboration, digital promotion, infrastructure development, and community empowerment in tourism development strategies to increase Own-Source Revenue. This study provides a contextual and integrated tourism development framework specifically for Bandar Lampung City, which has rarely been explored comprehensively in previous tourism development and regional income studies.